ON THE RELATIONSHIP BETWEEN DOMESTIC INVESTMENT, EXPORTS AND ECONOMIC GROWTH: EVIDENCE FROM GREECE - Sayef Bakari (Journal of Smart Economic Growth, 2022)
The aim of this paper is to investigate the relationship among domestic investment, exports and economic growth in the case of Greece. To attempt our goal, we used annual data over the period 1970 – 2020 and Vector Error Correction Model. Empirical results indicate that in the long run there is no causality relationship between exports, domestic investment, and economic growth. In the short run, we found that only exports cause domestic investment. These results proved as evidence that domestic investment and exports are not seen as a source of economic growth in the case of Greece which also explain the catastrophe situation of economic activity in Greece.